Central Line–Associated Bloodstream Infections in Children With Hematologic and Oncologic Diseases: First Prevalence Results From a University Hospital. (September 2019) - Özalp Gerçeker, Gülçin; Yardımcı, Figen; Aydınok, Yeşim
Central line–associated bloodstream infections (CLABSIs) are still a major cause of morbidity and mortality in pediatric hematology-oncology patients in many countries. This cross-sectional study was a retrospective review of CLABSI in inpatient pediatric hematology-oncology cases with long-term central venous catheter at the Pediatric Hematology Department from January 2013 to June 2014. Characteristics of CLABSI events in pediatric patients with hematologic malignancies and related nonmalignant hematologic conditions are documented. CLABSI developed in 61.8% ( n = 21) of the 34 hospitalized patients included in the study. The CLABSI rate was 7.8 per 1, 000 inpatient central venous catheter days. Coagulase-negative staphylococci was the predominant pathogen in 47.6% of the patients with CLABSI. The high rate of CLABSI requires prevention strategies to reduce CLABSI immediately. This study provides guidance in prioritizing strategies for reducing rates of infection.